Towards a Liquid Self: How Time, Geography, and Life Experiences Reshape the Biological Identity - Grignolio, Andrea; Mishto, Michele; Faria, Ana Maria Caetano; Garagnani, Paolo; Franceschi, Claudio; Tieri, Paolo (Frontiers in Immunology, 2014)
The conceptualization of immunological self is amongst the most important theories of modern biology, representing a sort of theoretical guideline for experimental immunologists, in order to understand how host constituents are ignored by the immune system (IS). A consistent advancement in this field has been represented by the danger/damage theory and its subsequent refinements, which at present represents the most comprehensive conceptualization of immunological self. Here we present the new hypothesis of "liquid self" which integrates and extends the danger/damage theory. The main novelty of the “liquid self” hypothesis lies in the full integration of the immune response mechanisms into the host body’s ecosystems, i.e. in adding the temporal, as well as the geographical/evolutionary and environmental, dimensions, which are synthetically expressed by what we suggested to call "immunological biography". Our hypothesis takes into account the important biological changes occurring with time (age) in the immune system (including immunosenescence and inflammaging), as well as changes in the organismal context related to nutrition, lifestyle and geography (populations). We argue that such temporal and geographical dimensions impinge upon, and continuously reshape, the antigenicity of physical entities (molecules, cells, bacteria, viruses), making them switching between "self" and "nonself" states in a dynamical, "liquid" fashion. Particular attention is devoted to oral tolerance and gut microbiota, as well as to a new potential source of unexpected self epitopes produced by proteasome splicing. Finally, our framework allows the set up of a variety of testable predictions, the most straightforward suggesting that the immune responses to defined molecules representing potentials antigens will be quantitatively and qualitatively quite different according to the immuno-biographical background of the host.